Zeolitic Materials with Hierarchical Porous Structures - Lopez-Orozco, Sofia; Inayat, Amer; Schwab, Andreas; Selvam, Thangaraj; Schwieger, Wilhelm (Advanced materials (Weinheim), 2011)
During the past several years, different kinds of hierarchical structured zeolitic materials have been synthesized due to their highly attractive properties, such as superior mass/heat transfer characteristics, lower restriction of the diffusion of reactants in the mesopores, and low pressure drop. Our contribution provides general information regarding types and preparation methods of hierarchical zeolitic materials and their relative advantages and disadvantages. Thereafter, recent advances in the preparation and characterization of hierarchical zeolitic structures within the crystallites by post‐synthetic treatment methods, such as dealumination or desilication; and structured devices by in situ and ex situ zeolite coatings on open‐cellular ceramic foams as (non‐reactive as well as reactive) supports are highlighted. Specific advantages of using hierarchical zeolitic catalysts/structures in selected catalytic reactions, such as benzene to phenol (BTOP) and methanol to olefins (MTO) are presented. Hierarchical zeolitic materials have attractive properties, such as superior mass/heat transfer characteristics, lower restriction of the diffusion of the reactants in the mesopores, and low pressure drop. Our Progress Report provides general information about the recent advances in the preparation and characterization of hierarchical zeolitic structures combining two (e.g., micro–meso, micro–macro) or even three (micro–meso–macro) levels of porosity.